Characterization of the CYP2D6 gene locus and metabolic activity in Indo- and Afro-Trinidadians: discovery of novel allelic variants. (February 2013) - Montané Jaime, Lazara Karelia; Lalla, Anthony; Steimer, Werner; Gaedigk, Andrea
Background: The highly polymorphic CYP2D6 gene has extensively been studied in many populations, but there is a void of knowledge regarding CYP2D6 pharmacogenetics and activity in populations with unique ancestries and admixture, such as those residing in Trinidad and Tobago.Materials & methods: 167 healthy Indo- and 103 Afro-Trinidadians were phenotyped with dextromethorphan and extensively genotyped. Gene resequencing was performed to resolve cases with genotype/phenotype discordance.Results: CYP2D6 activity did not differ between the Indo-Trinidadians and Afro-Trinidadians. Poor metabolizers were, however, more frequent in the Indo-Trinidadians (4.19 vs 1.94%), and unique allele frequency patterns were observed. Two novel nonfunctional allelic variants were found among the Indo-Trinidadians in two discordant cases. CYP2D6*100 is characterized by a single nucleotide deletion and CYP2D6*101 by a 19-bp deletion; both cause frameshifts.Conclusion: Our study underscores the importance of thoroughly characterizing the genetic make up of unique populations when considering pharmacogenetic testing for individualized therapy. Original submitted 15 October 2012; Revision submitted 7 December 2012